2015
DOI: 10.1017/s0021859614001361
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pre-natal stress on offspring development in pigs

Abstract: SUMMARYIn farm animals, restricted housing conditions or inadequate management practices during gestation may be potential stressors for the mother, with possible consequences on the growth, vitality, health and welfare of the dam and its offspring, and thus can have economic as well as ethical implications. The current review summarizes data from studies in pigs on the impact of maternal stress during gestation on the litter characteristics and phenotypic traits of offspring. The outcomes from the different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 59 publications
(128 reference statements)
1
21
0
3
Order By: Relevance
“…Studies in cattle are very scarce, but Lay et al (1997) showed that repeated transportation of Brahman cows during gestation increased the cortisol response of the progeny to an acute restraint stress. Otten et al (2015) reviewed prenatal stress studies in pigs and concluded that fetal brain regions relating to HPA function appear highly vulnerable to maternal stress and many studies have demonstrated changes in HPA function in postnatal life as a consequence of PNS (e.g. Otten et al 2010).…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…Studies in cattle are very scarce, but Lay et al (1997) showed that repeated transportation of Brahman cows during gestation increased the cortisol response of the progeny to an acute restraint stress. Otten et al (2015) reviewed prenatal stress studies in pigs and concluded that fetal brain regions relating to HPA function appear highly vulnerable to maternal stress and many studies have demonstrated changes in HPA function in postnatal life as a consequence of PNS (e.g. Otten et al 2010).…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
“…Across several studies (for a review, see Otten et al 2015), maternal stress has been found to have a negative effect on various behavioural domains important for piglet productivity and welfare, including pain responses (Rutherford et al 2009), reactivity (Kranendonk et al 2006b;Otten et al 2007), social behaviour (Jarvis et al 2006;Kranendonk et al 2006b) and maternal behaviour (Jarvis et al 2006;Rutherford et al 2014). In the latter study (Rutherford et al 2014), impairment of maternal behaviour had a significant effect on survival in the next generation; under conditions (free farrowing) where gilts could fully express their maternal behaviour, litters born to mothers that had been prenatally stressed had threefold the mortality of litters born to control mothers.…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
“…Partly this is of course because the field is relatively young and direct practical relevance is often not the primary motivation of those conducting the study. Based on these reviews, along with others recently conducted in cattle (Arnott et al 2012), poultry (Dixon et al 2016) and pigs (Otten et al 2015), where similar issues exist, it is possible to provide some suggestions for a way forward. These relate to: i) the choice of treatments, ii) the choice of outcome measures and iii) possible factors that may modify the effects of prenatal challenge on welfare outcomes.…”
Section: Suggestions For Future Research Work and Strategiesmentioning
confidence: 94%
“…Estudios han mostrado que el manejo temprano de los animales incluida la estimulación táctil, tiene efectos positivos sobre su desarrollo físico y psicológico (Fernández-Teruel et al, 2002). Por otro lado, se ha visto que en roedores y en otras especies el periodo prenatal y posnatal es una etapa crítica en su desarrollo (Otten et al, 2015). Por ejemplo, se sabe que las experiencias adversas como el estrés durante…”
Section: Methodsunclassified
“…Fernández-Teruel et al, 2002). On the other hand, it has been observed that in rodents and other species, the pre-and post-natal periods are crucial steps in their development (Otten et al, 2015). Revista Bio Ciencias 7, e789.…”
Section: Methodsmentioning
confidence: 99%